Subsystems of the Galactic halo, their structures and compositions - Marsakov, V. A.; Borkova, T. V. (Одеські астрономічні публікації, 2017)
It is shown that general populations of globular clusters and metal-poor field stars are components at least of three subsystems occupying different volumes in the Galaxy. The thick disk and proto-disk subsystems are genetically associated with the Galaxy. The age distributions of these two subsystems do not overlap. It is argued that heavy-element enrichment and the collapse of the proto-galactic medium occurred mainly in the period between the formation of the proto-disk halo and thick disk subsystems. The largest third subsystem has no metallicity gradient, most of its objects have retrograde motion in the Galaxy, some of them have unusually low content of a-elements, and their ages are comparatively low in average, supporting the hypothesis that the objects in this subsystem had an extragalactic origin.